Determination of Copper and Lead and Study their Poisonous Effects in Drinking Water in Baghdad - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The objective of this study is to determine the concentration of copper and lead (mg/L) in drinking water by using absorption spectrophotometic and Atomic Absorption spectrophotometric method from different area in Baghdad and with different intervals , The results show that the concentration of copper and Lead ( mgL) in tap water which remains motionless in plumbing system for following periods one hours, 3 hours, 6 hours, 12 hours, 24 hours, 7 days and 14 days are (1 , 2.2 , 4 , 5.3 , 7.5 , 10 and 16 mgL copper ) & ( 0.3, 0.5 , 0.8 , 1 , 2.5 , 3 , 3.8 mg /L lead ) respectively .from these results its clear that high levels of copper & Lead occur if tap water comes in contact with copper - lead plumbing and copper lead -containing fixtures in the water distribution system. If tap water remains motionless in the plumbing system for some time. These amounts of copper and Lead are believed to give rise to the symptoms of chemical food poisoning precipitated by the ingestion of alcohol on an empty stomach ( in presence of copper ). Also children under one year of age are more sensitive to copper than adults. Long-term exposure (more than 14 days) to copper - lead in drinking water which is much higher than 1,000 ug/I has been found to cause kidney and liver damage in infants, In case of Lead it can effect a children physical development & ability to learn.